Assessing readiness for knowledge management implementation in mental hospitals, Indonesia - Rohajawati, Siti; Akbar, Habibullah (International Journal of Engineering and Technology, 2021)
For Southeast Asiaâ€™s largest population, the prevalence of the emotional disorder has increased from 6% in 2013 up to 9.8% in 2018. Aligned with the e-government program, Knowledge Management (KM) offers an easier, faster, and transparent mental health services. However, the implementation relies on various factors. We conducted a workshop at 7 (seven) mental hospitals. The questionnaires were used to identify the factors that consist of awareness & commitment, strategy, culture, structure, people, and information technology (IT). We examine the hypothesis factors of the relationship by employing the statistical analyses of correlation. This study provides at testing the relationship between factors of people, process, and technology, for KM implementation in Indonesian mental hospitals. The results of the study confirm that the relationship between Process to Technology and People has a positive effect on significance. Meanwhile, the adop-tion of the existing technical facilities have not significant support for the needs of the KM. To sum up, the study suggests further improve-ment of leadership and systems in order to serve the best of mental healthcare.Â Â